The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s40360-019-0325-7
|View full text |Cite
|
Sign up to set email alerts
|

Potential drug-drug interactions among pneumonia patients: do these matter in clinical perspectives?

Abstract: Background Pneumonia patients are usually hospitalized due to severe nature of the disease or for the management of comorbid illnesses or associated symptoms. Such patients are prescribed with multiple medications which increase the likelihood of potential drug-drug interactions (pDDIs). Therefore, in this study the prevalence, levels (severity and documentation), predictors (risk factors), and clinical relevance of pDDIs among inpatients diagnosed with pneumonia have been investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 38 publications
1
24
1
5
Order By: Relevance
“…While Additional file 2: Table S2 and Additional file 3: Table S3 enlists most prevalent anti-microbial agents (AMAs) and drugs besides AMAs, respectively. Artesunate (n = 378), quinine (63), artemether (26), lumefantrine (23), primaquine (18), amodiaquine (11), and chloroquine (9) were the commonly prescribed anti-malarial agents to these study patients (Additional file 2: Table S2).…”
Section: Prevalence Of Potential Drug-drug Interactionsmentioning
confidence: 99%
“…While Additional file 2: Table S2 and Additional file 3: Table S3 enlists most prevalent anti-microbial agents (AMAs) and drugs besides AMAs, respectively. Artesunate (n = 378), quinine (63), artemether (26), lumefantrine (23), primaquine (18), amodiaquine (11), and chloroquine (9) were the commonly prescribed anti-malarial agents to these study patients (Additional file 2: Table S2).…”
Section: Prevalence Of Potential Drug-drug Interactionsmentioning
confidence: 99%
“…These findings are consistent with previously conducted studies. 6,14,15 Also, it has been evident from the study, the longer the duration of stay of patient in the hospital the more the risk of developing pDDI. This indirectly correlates to the number of medicines prescribed.…”
Section: Increase In Anti-hypertensive Effectmentioning
confidence: 87%
“…Study revealed very high prevalence of drug-drug interactions in the cardiac in-patients as supported by other studies. [4][5][6][7] The high prevalence may be due to presence of various risk factors in hospitalized patients. Elderly age group, cardiac illness and associated multiple co-morbidities which in turn lead to polypharmacy, may result into development of drug-drug interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential DDIs (pDDIs) issue has been addressed generally in hospitalized patients [7] as well as in specific diseases such as liver cirrhosis [11], hypertension [12], diabetes mellitus (DM) [13], bone marrow transplant [14], cancer [15], stroke [16], pneumonia [17], urinary tract infections [18], and hepatitis C [19]. Despite, being the most prevalent causes of hospitalization [20], DDIs particularly among inpatients with malaria remains unaddressed.…”
Section: Introductionmentioning
confidence: 99%